Determinants of the capital structure: a research on the manufacturing companies listed on the ISE 100 - Şişman, Seda (My University, 2006)
Kurumsal finansmanın ana konusu sermaye yapısıdır. Sermaye yapısı kararı borç ile özsermaye arasındadır. Sermaye yapısı özellikle yatırımların net bugünkü değerini hesaplamada iskonto oranı olarak da kullanılan ve önemli bir gösterge olan sermaye maliyetini etkiler. Artan borç oranı riskin artmasına sebep olur ki, bu da hissedarlar ve kredi sağlayanların bekledikleri getiriyi artırır. Optimum sermaye yapısı tezin ilk bölümünde anlatılmaktadır. Optimum sermaye yapısı şirketin çıkardığı bütün menkul değerlerin toplam pazar değerini maximize eden borç / sermaye oranıdır. İkinci bölümde sermaye yapısı konusundaki temel teoriler anlatılmıştır. Üçüncü bölümde ise sermaye yapısını etkileyen faktörler hakkında bilgi verilmiştir. Bu faktörler empirik çalışmaların incelenmesinden sonra belirlenmiştir. Dördüncü bölümde İMKB 100 endeksindeki üretim şirketlerinin sermaye yapıları 11 yıl için incelenerek bu faktörler tarafından belirlenip belirlenmediği test edilmiştir. Bu çalışmada regresyon analizi yöntemi kullanılmıştır. Sonuç olarak sadece altı şirket için anlamlı çıksa da geri kalan çoğu şirket için anlamlı bir sonuca ulaşılamamıştır. Şu an için İMKB şirketleri için maalesef 1992den beri olan datalara ulaşılabilmektedir. İleride yapılan daha kapsamlı çalışmalarla farklı sonuçlara ulaşılabilir. Sonuç olarak sermaye yapısı şirketler için çok önemli ve stratejik bir karardır.

The basic study of corporate finance is the capital structure. Capital structure choice is between debt and equity. Capital structure mainly affects the cost of capital, which can be used as an important indicator and a discount rate to calculate the net present values of the investment projects. Increasing leverage means increasing risk. It means increasing the required rates of return for both of common stockholders and the creditors. Optimal capital structure is explained in the first section of the thesis. Optimal capital structure is the optimal ratio of the securities, which maximizes the overall market value of all the securities issued by the firm. At the second section, the main theories on the capital structure are described. Mainly mentioned theories on capital structure are MM’ s Theory, Pecking Order Theory, Agency Theory and Converge to the Industry Mean Over Time. After the theories on the capital structure, the major commonly mentioned determinants of the capital structure are explained. These determinants are determined after investigation of empirical studies on capital structure. At the fourth section, a research is made on the determinants of the capital structure choice for the ISE 100 manufacturing companies. The hypothesis is the capital structure is defined by tangibility, market to book ratio, logarithm of sales, return on assets or return on equity, Times Interest Earned ratio and tax shield. The dependent variable is the capital structure, which means market debt to equity ratio. These determinants were tested with this research, but it failed for most of the selected companies. Some of the companies verified the theory with significant outputs but most of the companies outputs show that the hypothesis failed. As a conclusion, the firms should pay attention to their capital structure; it is a very important and a strategic decision for them.
Keywords: Muhasebe; Sermaye Piyasası